Studies of injection synthesis of composite functional layers of thin strip electrodes - Денисенко, Олександр Іванович (Technology audit and production reserves, 2012)
The paper describes the results of studies of the patterns of injection synthesis of metal composite functional layers of thin strip electrodes for lithium power sources at high energy exposures that accompany braking and penetration of accelerated in the supersonic flow microparticles of oxides into the metal surface